ASSESSING THE SOURCE OF KNOWLEDGE, ATTITUDE AND PRACTICE ON PUBERTAL AWARENESS AMONG PRE-PUBERTAL GIRLS : Pharmaceutical Science-Pharmacy Practice - JISHALA MI; PAVITHRA K; KANDASAMY, KRISHNAVENI; RAJAGOPAL, SHANMUGASUNDARAM; SAMBATHKUMARRAMANATHAN (International Journal of Life Science and Pharma Research, 2019)
A descriptive cross sectional study was conducted to evaluate the source knowledge, attitude and practice on pubertal awareness among pre-pubertal girls. A pre designed questionnaire which consists of questions to evaluate the knowledge, attitude and practice of pubertal awareness on pre-pubertal girls were used for data collection. Information on demographic variables which include age, class, type of family, education of parents, sources of information was collected from the participants. Total 450 prepubertal girls, 150 each from state board school, matriculation board school and central board school were included in the study. The study resulted that 52.6% of state board school participants major source of information were siblings, 64.6% of matriculation board and 68% of central board participants major source of information were mothers. The mean average level of knowledge was found to be (10%), attitude (23.5%) and practice (16.2%) for state board participants, for matriculation board participants the mean average level of knowledge (32.7%), attitude (58.3%) and practice (42.6%) and for central board participants the mean average level of knowledge (47.4%), attitude (59.6%) and practice (53.8%). Study concluded that most of the participants from central board school have good knowledge, attitude and practice regarding pubertal changes when compared with the state board and matriculation board, and the major source of information was mother for majority of study participants. The result demonstrated that based on parent’s literacy, the knowledge of girls on puberty increases. Creating awareness regarding puberty through health education is very essential to help the adolescent girls to handle sexuality related issues confidently.